Development and research for nanocomposite materials based on track templates of SiO2/Si - Даулетбекова, А.; Баймуханов, З.; Козловский, А.; Гиниятова, Ш.; Мурзагалиев, М.; Журкин, Е.; Наурызбаева, Р. (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2022)
In this paper, we present the results of the research for nanoclusters obtained by electrochemical deposition of zinc in track templates of a − SiO2/Si − n . The surface of the precipitated samples was examined with a scanning electron microscope JSM 7500F. X-ray diffraction analysis of the samples was carried out with an X-ray diffractometer D8 ADVANCE ECO using an X-ray tube with a Cu anode in the range of angles 2θ 30 ◦ -110 ◦ with step 0.01 ◦ . To identify the phases and study the crystal structure, we used the software BrukerAXSDIFFRAC.EVAv.4.2 and the international database ICDD PDF-2. During the electrochemical deposition of zinc in the track template of a−SiO2/Si−n , nanocrystals of zinc oxide were obtained in three crystalline phases: wurtzite, sphalerite, and rock salt structure. It should be noted that the type of the structure depends on the voltage applied to the electrodes. The optimal ECHO regime was established obtaining the most widespread phase of ZnO, wurtzite.